Uma UEPS para abordar a temática energia limpa visando a sustentabilidade - Pereira, Ana Paula dos Reis (2023)
The research presented in this dissertation is based on the need to promote Science teaching, especially themes related to energy sources and sustainability, in a contextualized manner, which enables the formation of concepts and their applications in everyday life. To this end, support was sought from the Theory of Meaningful Learning to present an alternative to teaching that favors memorization and memorizing the concepts studied in the classroom. From this perspective, the study outlined the objective of producing a didactic sequence - structured in the format of a Potentially Significant Teaching Unit (UEPS) - that contributes to the promotion of significant learning about solar energy towards sustainability. The research was guided by the following question: what are the contributions of a UEPS to promoting meaningful learning about solar energy with a view to sustainability? For the development of the investigation, an Educational Product was prepared with the proposal of a UEPS consisting of 11 meetings. This is a Pedagogical Intervention research, with a qualitative approach and carried out with a 9th year elementary school class from a private school, in the city of Rondonópolis, MT. As data collection instruments, associated with UEPS activities, records in the class diary, materials produced during the process of applying the sequence and the final assessment were used. Data analysis took place based on four categories, namely: Subsunçores; Pre-disposition to learn significantly; Progressive Differentiation and Integrative Reconciliation; Application of knowledge in new contexts. The data indicate that the proposal was able to identify the underlying concepts contained in the students' cognitive structures, regarding the topic addressed, to promote progressive differentiation and reconciling integration of concepts related to energy sources and sustainability, to keep students predisposed to learn significantly and apply the subjects studied in contexts different from those presented in the classroom, which means that the proposed UEPS can be considered potentially significant material and serves as support for Basic Education teachers. Finally, it is noted that the EP originating from this study is available at: http://educapes.capes.gov.br/handle/capes/741438.